FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP PEMERINTAH DAERAH DALAM MEWUJUDKAN APARATUR YANG BERSIH BEBAS DARI KORUPSI, KOLUSI DAN NEPOTISME DI KABUPATEN BOYOLALI - SUGITO, SUGITO (Dinamika Hukum, 2017)
This research gave a description on the implementation of supervisionconducted by The Regional House of Representatives (DPRD) on The RegionalGovernment in order to develop the implementation of a proportional supervisionby DPRD on the Regional Government, therefore the good governance can beembodied.Background: the background of the research focus is malfunction of thesupervision of DPRD on the Regional Leader along with the apparatuses causesthe proliferation of deviating behavior by the regional in the forms of uncleanactions and full of corruption, collution and nepotism (known as KKN). Thecentralization of power between the central government and the regionagovernment which is full of KKN causes a prolonged multi-dimentional crisis.This research is a juridical normative research. The selected location is inDPRD of Boyolali Regency. The characteristics of this research is descriptive thataccording to Soerjono Soekamto is â€œa research that provides an initial data ascarefully as possible about human, condition or other symptomsâ€. Object of thisresearch is The Supervisory Function of The Regional House of Representativeson The Regional Government in Creating A Clean Government Which is Freefrom Corruption, Collusion and Nepotism in Boyolali Regency. In this research,the writer used a qualitative method.The results of the research showed that the implementation of thesupervision conducted by DPRD on the Regional Government had tasksaccording to their field, therefore, the main task and function among themembersin conducting the supervision task had been suitable with the code ofconduct Number 1 of 2014 of DPRD of Boyolali Regency. The supervision isclosely related to supremacy, therefore it needs a support pillar that covers asystem of regulation, the legal implementation sistem, the legal supremacyofficers, and the judicature system. The decision whether to accept or to reject isappropriate to the provision of article 6 paragraph (4) of the Government RuleNumber 15 of 2015 that is considered as accepted. The main supervision shouldbe based on the implementation of APBD (the Regional Budget) in which itbecomes the responsibility of supervision by DPRD. The obstacles faced byDPRD of Boyolali Regency in implementing the supervisory function on theRegional Government are: 1) lack of understanding on the position, the task and the authority as well as the rights of DPRD; 2) the limitation in experience and oreducation in the legal and government field; 3) the limitation in understanding thestructure of relation among the government institutions; and 4) the attachment ofpersonal interest, group interest and political interest.Keywords: the supervision of DPRD and good government